The Impact of Direct Method Through 'Guess of Picture' on Improving Arabic Language Proficiency Among Students at Nurul Huda Islamic Primary School, Patihan Lamongan - Muzaki, Muhamad Iqbal; Qodir, Abdul (Universitas Al-Amien Prenduan, 2024)
Arabic is the language of the Qur'an and the language of Islam, with billions of followers worldwide. However, students nowadays are rarely interested in learning Arabic, which affects their learning outcomes. Therefore, the researcher is interested in examining the influence of the direct method using picture guessing on students' learning outcomes. The aim of this study is to determine the implementation, results, and influence of the direct method through picture guessing on Arabic learning outcomes at MI Nurul Huda Patihan Lamongan. The method used in this research is a quantitative method. The results of the study showed that the pre-test and post-test scores tested with the t-test resulted in a t-value greater than the t-table value, which was 12.954 > 2.042. This means that there is an influence of the direct method using picture guessing on students' learning outcomes.Keywords: Direct method; Arabic learning outcomes; Arabic language.